Caudolateral Orbitofrontal Regional Cerebral Blood Flow is Decreased in Abstinent Cocaine-addicted Subjects in Two Separate Cohorts - Adinoff, Bryon (2011)
The orbitofrontal cortex (OFC) is crucial for the inhibition of extraneous stimuli, evaluation of aversive information, and emotional regulation – all behaviors impaired in cocaine addiction. Previous studies suggest that cocaine-addicted subjects have decreased basal activity in the orbitofrontal cortex (OFC). In this study, we examined regional cerebral blood flow (rCBF) during a saline infusion in two independent populations of abstinent cocaine- (and mostly nicotine-) addicted (n=33 and 26) and healthy control (n=35 and 20) men and women. Isolated rCBF decreases (p<0.001) were observed in the left caudolateral OFC, as well as left superior temporal cortex, in cocaine-addicted subjects relative to controls in both cohorts and bilaterally in the combined cohort. An anatomically defined region of the caudolateral OFC showed similar findings and were evident in both male and female addicted subjects. The reliability of these findings across two cohorts reveals a functional disruption in the lateral OFC, a brain region implicated in the evaluation of behavior-terminating stimuli. This may contribute to an addicted individual’s persistent drug use despite negative consequences.